Platinum(II) Linkage Isomeric Complexes Containing Mixed Ligands 4,5-diphenyl-1,2,4-triazole-3-thione and Diphosphines Ph2P(CH2)nPPh2 (n = 1,2 or3) - H. ABDULLAH, BAYAZEED; A. ABDULLAH, MOHAMED; A. AL-JIBORI, SUBHI; A.K. AL-ALLAF, TALAL (Asian Journal of Chemistry, 2010)
Potassium salt of the ligand 4,5-diphenyl-1,2,4-triazole-3-thione (LK) reacts with K2PtCl4 to give trans-[PtL2], in which (L) behaves as a bidentate chelating ligand coordinated to platinum through the nitrogen atom no.2 of the triazole ring and the sulphur of the thiolate group. Reaction of trans-[PtL2] with the diphosphine Ph2P(CH2)n PPh2 (n = 1, 2 or 3) gave the mixed ligand complexes [PtL2(diphos)]. The produced isomers are either a single isomer, the S,S-bonded (when n = 1 or 3) or a mixture of two linkage isomers, the S,S-bonded and the N,N-bonded isomers (when n = 2). However, a reaction of [PtCl2(diphos)] with LK gave rather different isomers, two isomers in each case. The N,N- bonded and the N,S-bonded isomers, where n = 1 or 2 and the S,Sbonded and the N,S-bonded isomers where n = 3. The prepared complexes have been identified by elemental analysis, IR, UV/Vis, 1H and 31P NMR spectra. The 31P NMR data have been used effectively to identify the produced linkage isomers.